2003
DOI: 10.1063/1.1542935
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and modeling of the nitrogen passivation of interface traps in SiO2/4H–SiC

Abstract: The relationship between nitrogen content and interface trap density (Dit) in SiO2/4H–SiC near the conduction band has been quantitatively determined. Nitridation using NO significantly reduces Dit near the conduction band, but the effect saturates after ≈2.5×1014 cm−2 of nitrogen. These results are consistent with a model of the interface in which defects such as carbon clusters or silicon suboxide states produce traps with energies corresponding to the sizes of the defects. Nitrogen passivation results in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
59
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 17 publications
4
59
0
1
Order By: Relevance
“…Previously, it was believed that incorporated nitrogen atoms of $10 14 cm À2 were distributed in the oxide side of a nitrided SiO 2 /SiC interface. 12 However, our findings suggest a new model that nitrogen atoms are not only embedded in the oxide layer but also fixed in the SiO 2 / SiC interface region.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Previously, it was believed that incorporated nitrogen atoms of $10 14 cm À2 were distributed in the oxide side of a nitrided SiO 2 /SiC interface. 12 However, our findings suggest a new model that nitrogen atoms are not only embedded in the oxide layer but also fixed in the SiO 2 / SiC interface region.…”
mentioning
confidence: 50%
“…Although the reason for such a threshold remains unclear at present, a similar trend has been reported in a previous study. 12 Finally, the reason why nitrogen atoms incorporated into the SiO 2 /SiC interface region are not removed by HF etching is discussed. There are two possible mechanisms that fix nitrogen atoms in the interface region.…”
mentioning
confidence: 99%
“…Furthermore, for nitrided oxides, XPS showed that the complex suboxide and oxide-carbon bonds were removed, thus being accompanied by the formation of strong Si N bonds and the significant reduction of the spectral intensity of C-C bonds [127]. Mc Donald et al [128] studied the reduction of the interface states density by NO-nitridation, observing a saturation effect upon a nitrogen incorporation level of 2.5×10 14 cm 2 . The presence of such saturation is consistent with a model of the interface in which large clusters composed of an excess of interfacial carbon or silicon are subsequently passivated (and dissolved) by the indiffusing nitrogen, with the formation of strong C N and Si N bonds.…”
Section: Interface Transport Properties In the Sio 2 /Sic Systemmentioning
confidence: 99%
“…하지만 SiC/SiO2 구조는 Si/SiO2 대비 계면 포획 밀도가 약 100배 수준으로 높기 때문에 MOSFET 제작에 응용 할 경우 반전 채널에서의 전자 이동도가 5cm 2 /Vs 수 준으로 낮아 전류 구동 능력이 물성의 기대치에 현저 히 못 미치는 문제점을 가지고 있다 [3] . 질소-패시베이 션을 이용하여 계면 포획 농도를 감소시키는 방법이 잘 알려져 있지만, SiC의 표면에서 SiO2를 성장시킬 때 형성되는 구조적 결함들을 모두 해결할 수 없다는 한계 또한 존재하고 있다 [4] . 이에 다른 산화막 물질 [5] , 산화막을 형성하는 다른 방법 [6] 및 질소-패시베이션 의 대체 공정 개발 [7], [8] 등 다양한 방향으로 SiC/SiO2…”
unclassified